Islamic Counseling Interventions for Managing Parent–Teen Conflict Related to Social Media Use and Online Friendships - Nabilaa Faizatuz Zuhriyah (Islamic Counseling and Parenting Journal, 2025)
The rapid growth of social media has intensified parent–teen conflict in many Muslim families, particularly concerning online friendships, privacy, and moral risks. While existing digital parenting frameworks address behavioral concerns, they often overlook the cultural and religious dimensions that shape family dynamics in Islamic contexts. This study aims to explore how Islamic counseling principles can be integrated to manage and reduce parent–teen conflict related to social media use. Using a qualitative phenomenological design, data were collected from ten Muslim parent–teen dyads through semi-structured interviews, observations, and document analysis, followed by thematic analysis. The findings indicate that conflict is driven by contrasting interpretations of digital autonomy, moral expectations, and online peer interactions. Adolescents view social media as an essential space for identity exploration, while parents perceive it as a potential moral threat. Islamic counseling was found to facilitate conflict resolution by providing a shared moral language, improving emotional communication, and fostering trust-based negotiation. The study concludes that integrating Islamic values—such as adab, amanah, and shura—with evidence-based counseling practices offers a culturally grounded framework for improving family harmony and guiding digital behavior. These insights have significant implications for counselors, educators, and policymakers in Muslim communities.